If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = -5x + -5 + 6x Reorder the terms: -2 = -5 + -5x + 6x Combine like terms: -5x + 6x = 1x -2 = -5 + 1x Solving -2 = -5 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2 + -1x = -5 + 1x + -1x Combine like terms: 1x + -1x = 0 -2 + -1x = -5 + 0 -2 + -1x = -5 Add '2' to each side of the equation. -2 + 2 + -1x = -5 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = -5 + 2 -1x = -5 + 2 Combine like terms: -5 + 2 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3
| 3u=-34-2u | | b^2+6b(0.5)=36 | | 30(2/15) | | 30•2/15 | | 24=6b-4 | | 13=6(x-7)+8 | | 6x+7=2x-37 | | 7b+4a-3a-5b= | | 1.1666x=140 | | 37=5+8x | | 3512/4= | | 11x+3=2x-5 | | X*(2X+5)=25 | | x^3+8x^2-3x-2266=0 | | 4x=3512 | | 1=5(3)+b | | 13x-3y=34 | | 5x^2=2.2x^2+5.88x+3.168 | | 64*3.14= | | 8/6=5/9 | | 3=-1x+1y | | p(5)=1.8 | | n/32=512 | | a^17/4a^9 | | 360=x(x+2) | | 65=2+7x | | 40-2.5x=3 | | 3(p+7)=2(p-3)+p+27 | | h(5)=175(1.028)5 | | 0.4(x-0.45)=9.2 | | 5+8=43 | | Z/5w=8 |